The Effect of Health Education with Pop – Up Book Media on Increasing Adolecent Knowledge Related to Premenstrual Syndrome in SMP Negeri 6 Jember - Dwi Setya Damayanti; Dini Kurniawati; Eka Afdi S (Fakultas Kedokteran, 2022)
Premenstrual Syndrome is a collection of symptoms that occur in women usually 6-10 days before menstruation begins and will disappear by itself when menstruation has started. Premenstrual syndrome is also an unpleasant symptom, both psychologically and physically, which occurs in women before their menstrual period. Lack of knowledge about premenstrual syndrome in young women can have an impact on readiness or unpreparedness in overcoming the symptoms of premenstrual syndrome which can sometimes have a negative impact on daily activities. The purpose of this study was to determine the effect of providing health education using pop-up book media related to the knowledge of young women about premenstrual syndrome. The research design used was pre-experimental with a one-group pre-test and post-test design approach. The method of sampling the data was cluster random sampling, with the number of respondents as many as 77 young women SMP Negeri 6 Jember. The data were analyzed using univariate and bivariate, and the results of the paired sample t-test showed that there was a significant effect before and after being given treatment with a sig value. (2-tailed) of 0.000 or <0.05. Based on the results of the research, it can be concluded that there is an effect of providing health education using pop-up book media on the knowledge of young women regarding premenstrual syndrome.